PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE NUMBERED HEADS TOGETHER (NHT) BERBANTUAN WORDWALL TERHADAP HASIL BELAJAR PENDIDIKAN PANCASILA DI SEKOLAH DASAR - Nurhidayah; Syarif, Irman; Wulandari (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to determine the effect of implementing the cooperative learning model of the Numbered Heads Together (NHT) type assisted by Wordwall media on students’ learning outcomes in Pancasila Education on the topic "Indonesian Cultural Diversity (Sulawesi Island)" for fifth-grade students at SDN 79 Gura. The research used an experimental design with a one-group pretest-posttest design involving 17 students as subjects. Data collection used learning outcome tests in the form of pretests and posttests, while data analysis was conducted through descriptive and inferential statistics, including normality tests (Shapiro-Wilk), paired sample t-tests, and N-Gain tests. The results indicate a significant effect on students’ learning outcomes, evidenced by an increase in average scores from 57.06 (pretest) to 78.24 (posttest). The paired sample t-test showed a significance value of 0.000 < 0.05, meaning H1 was accepted. Student mastery increased from 23.53% to 76.47%. The N-Gain score of 0.4895 (48.95%) places the result in the moderate category, indicating the model is fairly effective. These findings suggest that the NHT cooperative learning model assisted by Wordwall can serve as an effective and innovative alternative for improving Pancasila Education learning outcomes in elementary schools.